2009
DOI: 10.1016/j.pmrj.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning of a Gait Pattern to Reduce Forefoot Plantar Pressures in Individuals with Diabetic Peripheral Neuropathy

Abstract: Individuals with diabetic peripheral neuropathy were unable to use a "new" strategy gait pattern to reduce peak plantar pressures long term (1 week). The use of visual feedback following the trial did not assist in the learning of a new walking pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 17 publications
0
40
1
9
Order By: Relevance
“…Previous studies do not describe the foot rollover changes after such a specific set of exercises for foot and ankle [24-27]. Usually, attention is mostly given to PP and PTI reduction as a target to reduce the risk of ulceration, but these variables should be analyzed together with several other risk factors [4,5,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies do not describe the foot rollover changes after such a specific set of exercises for foot and ankle [24-27]. Usually, attention is mostly given to PP and PTI reduction as a target to reduce the risk of ulceration, but these variables should be analyzed together with several other risk factors [4,5,36].…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have described the subtle, positive effects of foot and ankle exercises in this population, although some studies were not randomized controlled trials [24,25], and others reported on quite short interventions and follow-up periods [26,27]. Therefore, there are still not enough data for conclusions to be arrived at regarding the effectiveness of such interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions that focused on foot and ankle recovery and their impact on gait have presented partially good outcomes [60-62]. Some improvement in balance and confidence in a population with DPN was shown by Richardson et al [60].…”
Section: Introductionmentioning
confidence: 99%
“…Parmi elles, des capteurs de pression plantaire [13][14][15][16][17][18][19][20][21][22][23][24], les accéléromètres [25][26][27][28][29][30][31][32][33][34][35][36][37], les goniométres [38][39], les systèmes optoélectro-niques [40][41]. Cependant, ces technologies sont limitées au laboratoire de recherche et sont peu adaptées à une utilisation « grand public ».…”
Section: Introductionunclassified